2020
DOI: 10.1038/s41598-020-57698-0
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of SENP2 in Multiple Myeloma Induces Bortezomib Resistance by Activating NF-κB Through the Modulation of IκBα Sumoylation

Abstract: The proteasome inhibitor bortezomib is the most successfully applied chemotherapeutic drug for treating multiple myeloma. However, its clinical efficacy reduced due to resistance development. The underlying molecular mechanisms of bortezomib resistance are poorly understood. In this study, by combining in silico analysis and sgRNA library based drug resistance screening assay, we identified SENP2 (Sentrin/SUMO-specific proteases-2) as a bortezomib sensitive gene and found its expression highly downregulated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“… 28 In addition, the MEK/ERK pathway cascade is associated with RAS/RAF mutations, further driving mutation-inducing MM, and the activation of NF-κB is critical in supporting MM cell growth as well as in the formation of drug resistance. 19 , 29 Therefore, we speculated that PKD1 might be upregulated and associated with clinical characteristics in patients with MM, while the related evidence is lacking. First, we found that PKD1 mRNA and protein expressions were both increased in patients with MM compared with HCs and presented good value in distinguishing patients with MM from HCs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 28 In addition, the MEK/ERK pathway cascade is associated with RAS/RAF mutations, further driving mutation-inducing MM, and the activation of NF-κB is critical in supporting MM cell growth as well as in the formation of drug resistance. 19 , 29 Therefore, we speculated that PKD1 might be upregulated and associated with clinical characteristics in patients with MM, while the related evidence is lacking. First, we found that PKD1 mRNA and protein expressions were both increased in patients with MM compared with HCs and presented good value in distinguishing patients with MM from HCs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, according to the prior evidence, PKD1 has regulatory effect on NF-κB and JNK signaling, and drug resistance to bortezomib is associated with stimulation of NF-κB signaling but inactivation of JNK signaling. 11 , 19 , 20 Moreover, PKD1 activates MEK/ERK signaling cascade, which is associated with RAS/RAF mutations, which is involved in the development of drug resistance in MM treatment. According to these aforementioned evidence, we speculated that PKD1 might be correlated with prognosis in patients with MM treated with bortezomib-based regimens and found that PKD1 was negatively associated with treatment response and survival with regard to bortezomib-based treatment in patients with MM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SENP2 has a broad substrate specificity similar to SENP1 [ 159 ]. Silencing of SENP2 in MM contributes to the development of bortezomib resistance mediated by the activation of NFκB [ 160 ]. Similarly, it has been shown in other cancers that activation of NFκB may also induce resistance to therapy [ 160 ].…”
Section: Desumoylationmentioning
confidence: 99%